2023
DOI: 10.1111/hel.12964
|View full text |Cite
|
Sign up to set email alerts
|

Gastric microbiota in gastric cancer and precancerous stages: Mechanisms of carcinogenesis and clinical value

Abstract: Gastric cancer (GC) is a globally important disease. The discovery of Helicobacter pylori (H. pylori) demonstrated that the human stomach is not a sterile environment, and recent advances in molecular biology have led to the detection of large populations of microorganisms in the stomach. A growing number of studies have elucidated differences in the microbiota of patients at various stages of GC development. Evidence from insulin‐gastrin transgenic (INS‐GAS) and human gastric microbiota‐transplanted mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 103 publications
(250 reference statements)
0
7
0
Order By: Relevance
“…It has been observed that probiotics can lower the risk of gastric cancer by inhibiting H. pylori. 86 As reported by He and colleagues, 105 3).…”
Section: Regulation Of the Microbiotamentioning
confidence: 81%
See 1 more Smart Citation
“…It has been observed that probiotics can lower the risk of gastric cancer by inhibiting H. pylori. 86 As reported by He and colleagues, 105 3).…”
Section: Regulation Of the Microbiotamentioning
confidence: 81%
“…It has been observed that probiotics can lower the risk of gastric cancer by inhibiting H. pylori 86 . As reported by He and colleagues, 105 probiotics could attenuate gastric inflammation induced by H. pylori by modulating pro‐inflammatory pathways such as TNF, IL‐17, and NF‐κB signaling pathways.…”
Section: Clinical Applications and Future Perspectivesmentioning
confidence: 82%
“…All of these data suggest that the gastric microbiota in addition to H. pylori plays a role in the latter stages of gastric carcinogenesis[ 22 ]. Furthermore, data derived from experiments in transgenic mouse models with insulin-gastrin transplantation and human gastric microbiome support the view linking the gastric microbiota to GC development[ 19 , 23 ]. Finally, it appears that the colonic microbiota favors GC development through various metabolites.…”
Section: Etiopathogenesismentioning
confidence: 87%
“…Microbial taxonomic features (MTFs) can be used to predict early gastric neoplasia (EGN; Png et al, 2022 ) and may improve the accuracy of the polygenic risk score (PRS) model in predicting GC ( Wang et al, 2023 ). As for the mechanism, many studies have revealed that non- H. pylori microorganisms promote GC by inducing inflammation, modulating the immune response, triggering DNA damage, and promoting epithelial–mesenchymal transformation ( Yang et al, 2022 ; Liao et al, 2023 ). Gastric non- H. pylori microorganisms may participate in the progression of GC by affecting host DNA methylation ( Yue et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gastric non- H. pylori microorganisms may participate in the progression of GC by affecting host DNA methylation ( Yue et al, 2023 ). Different bacterial taxa are related to certain types of infiltrating immune cells ( Liao et al, 2023 ). In the gastric microbiota associated with atrophy/intestinal metaplasia, functional pathways such as amino acid metabolism and inositol phosphate metabolism are enriched, while folate biosynthesis and NOD-like receptor signaling are reduced, which may explain the ongoing progression of precancerous conditions even after H. pylori eradication ( Sung et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%